Daya Terima dan Viskositas Formula Enteral Berbasis Pangan Lokal - Ibnu Zaki; Gumintang Ratna Ramadhan; Widya Ayu Kurnia Putri (Poltekkes Kemenkes Semarang, 2024)
Background: Pumpkin, purple sweet potato, catfish, and soybean tempeh contain nutritional elements beneficial for health. These ingredients, formulated into enteral formulas, are expected to serve as potential nutritional therapy for malnutrition.Objectives: This study aims to explore the hedonic aspects, hedonic quality, and viscosity of enteral formulas made from pumpkin, purple sweet potato, catfish, and soybean tempeh.Method: This research employed a Randomized Complete Block Design (RCBD) consisting of four treatments labeled as L1, L2, L3, and L4 with consecutive ratios of catfish flour to soybean tempeh flour being 19:31, 21:29, 23:27, and 25:25. Hedonic and hedonic quality were analyzed using the Friedman test, while viscosity was analyzed using the One-Way ANOVA test.Results: The research results indicate a significant influence (p<0.05) on viscosity and hedonic quality tests for color and thickness parameters, as well as hedonic tests for taste and aroma parameters. However, there is no significant influence (p>0.05) on hedonic quality tests for taste and aroma parameters and hedonic tests for color and thickness parameters.Conclusion: The highest average results in hedonic and hedonic quality tests were found in enteral formula L1. The panelists favored enteral formula L1, which had the least amount of catfish flour and the most soybean tempeh flour. The enteral formula with the best hedonic quality was also identified as formula L1. As the proportion of added catfish flour increased, the viscosity of the enteral formula also increased.